Risk of Bias in Randomized Controlled Trials: An Analysis of Parent-Targeted Postnatal Education Interventions from Low and Middle-Income Countries - Dol, Justine; Beniot, Britney; Richardson, Brianna; Tomblin Murphy, Gail; Aston, Megan; McMillan, Douglas; Gahagan, Jacqueline; Campbell-Yeo, Marsha (Global Health: Annual Review, 2020)
Randomized controlled trials (RCTs) are vulnerable to internal and external bias, particularly when examining complex health behavioural interventions. The effects of postnatal education interventions on parent’s knowledge of caring for their newborn in low-and middle-income countries (LMICs) is a growing area of study. Therefore, the aim of this review was to assess the risk of bias (RoB) in such studies. MedLine, CINAHL, and SCOPUS were searched from January 2000 - October 2017 using key words such as RCT, parent-targeted, postnatal, education, interventions, and LMICs. Two reviewers screened title and abstracts and full text of eligible studies. Outcomes of interest were RoB measured using the Cochrane RoB tool, as well as intervention fidelity and contamination bias. Data were descriptively analyzed with 29 RCTs included. Highest risk of bias was in participant (55%) and personnel (76%) blinding with the lowest risk of bias in random sequence generation (76%), and attrition bias (72%). Overall, 89.7% of studies on postnatal parent-targeted education interventions in LMICs had a high RoB score in at least one domain. While difficult to avoid such biases, opportunities can be sought to minimize these during the design and conduct of future studies in this area.